CEBUANO-BISAYA UTTERANCES OF GRADE 2 PUPILS - Rowanne Marie Maxilom -Mangompit; Florence Mae Bornales; Shoji Nakazawa (Universitas Muhammadiyah Surakarta, 2020)
This paper aimed at clarifying and further establishing the Cebuano – Bisaya language through a descriptive analysis of the Cebuano-Bisaya utterances of Grade Two pupils from Don Bosco Technology Center during their Mother Tongue class. Moreover, the study determined the Typological Linguistic Universals by Greenberg (1963) applicable to Cebuano, Tanangkingsing’s (2009) Nonverbal clauses, and Pesirla’s (2010) Verb Predicate forms and Content Words existent in the utterances. The study was a descriptive analysis of two regular classroom sessions or two 40-45 minute class between the Mother Tongue teacher and 45 pupils who were all boys. Interesting results were found such as the use of only three kinds of nonverbal clause, the dominance of nouns in their utterances, the existence of all kinds of verb predicates, and the application of 3 out of 6 typological linguistic universals. The results were taken from a teacher – pupils discourse under the supervision of the said academe. Keywords: Cebuano, clauses, linguistic universals, typology, utterances